PENCIPTAAN PROGRAM TELEVISI EKSPRESI ORANG KAMPUNG - Rahmad, Cito Yasuki (Acintya, 2014)
Motivation and the inspiring theme in documentary television programs are very popular broadcastedin our television. Public like these programs because they provide educational values to thepublic especially related to the value of spirit, togetherness and the desire to achieve the goals. Thiskind of program has raised many pioneering figures that inspire audience.The problem is the narrator or the narration of that program that always be performed by thirdperson, i.e. a reporter or presenter. The reporter or presenter here often only fulfills the market needs:she/he is beautiful or handsome, and she/he sounds tuneful. She/he only presents the story about thesubject, but she/he dominates it. Although this method can help to promote the programs and help theproduction technique team but this method is potential to bring two biases. First, the presenter doesnâ€™thandle the atmosphere around the subject. Second, the presenter maybe presents the subject in thewrong way. So we create this documentary television project â€œVillagerâ€™s Expressionsâ€ in order to tryto solve the problems. This project mixes the standard production pattern of documentary televisionprogram with the production pattern of video participatory: the subject tells their own stories bythemselves and with their own point of view.As an experimental project, we present the first episode: â€œAWI, Children (villagerâ€™s) Theaterâ€. AWI isa children theater community that is based on kampong Merganser Kidul, Yogyakarta which hasexisted in Yogyakarta during 2000s. We present this episode beside the above reason and we alsowant to open the stagnation of documentary television program, especially about art and culturaltheme.Keywords: Expression media, Indigenous people, Inspirational TV program, video participant